Formulating Growth Guidelines in the Innovation Process: The Case of Mechanical Engineering SMEs - Masuda, Koji; Fujiyama, Kojiro; Haruyama, Shigeyuki (International Journal of Integrated Engineering, 2024)
In Japan and Germany, the mechanical engineering industry is a significant industrial sector, and the growth of small and medium-sized enterprises (SMEs), which constitute a large proportion of the number of firms and employees, has a considerable impact on a country’s growth. Innovation is an effective approach for firms to achieve growth. In this study, we propose that the phase of formulating growth guidelines, which include three factors: growth objectives, scope, and directions for growth, should be establish before the phase of implementing the innovation process. A new scope framework is constructed and a method for evaluating the consistency of the growth guidelines is presented. The method is applied to Japanese mechanical engineering SMEs that have achieved growth through innovation, and the applicability of the framework and the consistency of the growth guidelines are confirmed. This study provides an idea of growth guidelines that can be used to guide decision making in implementing the innovation process